Magnetotelluric inversion strategies. Issue 1 (1st December 2019) - Schaa, Ralf; Harris, Brett; Pethick, Andrew
Summary: Regional scale geophysical data is widely and publicly available in many countries. Traditionally, these data include transects that span many hundreds of line kilometres. More recently it was recognised that imaging deep three dimensional crustal structures requires new 3D data sets. An example of this is the Australia AusLAMP magnetotelluric grid. We consider this data from a different perspective and ask how sparse regional data can be incorporated in mineral exploration workflows which focus on the top few kilometres of the Earth. We select a reference area of about 100, 000 square kilometres in central Australia, which includes the 450 kilometre long Yilgarn Craton, Officer Basin, Musgrave Province (YOM) seismic and MT transect. We test and compare a number of 1D and 2D inversion strategies with broadband MT data and then stretch that geo-electrical model to the third dimension with an additional 18 long period MT stations on a 50 km grid in the Officer Basin and Musgrave block. With additional data from just a few sparse stations, such as those from the AusLAMP project, we show that the value and outcome of MT inversions can be enhanced. The search for new tier one mineral deposits is transitioning to the under explored deeper covered areas at basin margins, and we have demonstrated techniques for building 3D geo-electrical frameworks towards more relevant shallower exploration depths from including exceedingly sparse long period 3D MT data.